Markedly more women on executive boards of large companies: Inclusion requirement seemingly already having an effect - Anja Kirsch; Virginia Sondergeld; Katharina Wrohlich (DIW Weekly Report, 2022)
There was a significant increase in the number of women on executive boards of large companies in Germany from 2020 to 2021 after years of slow progress: In fall 2021, there were 139 women on the executive boards of the 200 largest companies, 38 more than in 2020. This is an increase of a good three percentage points to almost 15 percent, the largest seen since the beginning of the DIW Berlin Women Executives Barometer in 2006. There were also markedly more female executive board members on average in the DAX companies. The inclusion requirement for executive boards (Beteiligungsgebot für Vorstände), which was adopted in 2021 and comes into effect in August 2022, has clearly resulted in anticipation effects: The share of female executive board members of companies subject to the requirement has increased from a good 14 percent to a good 19 percent. In contrast, the share of female executive board members of companies not subject to the requirement only increased from 11 percent to around 14 percent. Similar to the gender quota for supervisory boards, this shows that statutory requirements are an effective instrument for increasing the share of women on boards. The momentum in supervisory boards, however, was markedly weaker in 2021 than in previous years.
Keywords: D22; J16; J59; J78; L21; L32; M14; M51; 330; corporate boards; board composition; boards of directors; board diversity; Europe; women directors; gender equality; gender quota; Germany; management; private companies; public companies; supervisory boards; executiveboards; CEOs; women; finance industry; financial sector; private and public banks; insurance companies